MODEL BELAJAR BERMAIN SOSIAL DALAM UPAYA MENINGKATKAN KECERDASAN EMOSI PESERTA DIDIK - Idris Saputra Simbolon; Srimaharani Tanjung; Irfan Tobing (Institut Pendidikan Tapanuli Selatan, 2022)
Developing Early Childhood Creativity Through Folding Games of Origami Paper in Kindergarten Nurul Huda Suka Maju Village Mestong District, Muaro Jambi Regency Role playing or fake play is a very good activity to improve children‟s emotional social intelligence, And build children‟s thinking power. These types of games include drama plays or role plays and other types of games where children play roles as other people. This type of research is a type of collaborative classroom action using the Kemmis model and the Taggart MC. The subject of this study were children of group B2, which amounted to 20 children consisting of 12 boys and 8 girls the data collection methods used were documentation observation and interviews. Role playing can improve children‟s emotional social intelligence and after action through role playing in the first cycle of meetings 1 percentage of the child‟s emotional social intelligence of 5% that developed very well in the first cycle of meeting 2 the percentage of children 30% developed very well in the second cycle of the meeting 1 the percentage of 50% of children‟s social emotional intelligence that developedvery well in the 2nd meeting cycle 2 the percentage of children as much as 85% that developed very well showed that the social emotional intelligence og group B 2 children with very goodcriteria had reached the indicator 85% success.